2023
DOI: 10.3390/c9010025
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Detection of Hydrogen Sulfide by Simple Cu-CNTs Nanocomposites

Abstract: The presented work is devoted to the preparation of nanocomposites based on multiwall carbon nanotubes (MWCNTs) and copper (Cu) nanoparticles by a simple chemical method, and to study their sensing properties to hydrogen sulfide (H2S) gas. The Cu decorated multiwall carbon nanotubes (MWCNTs/Cu) were prepared by the deposition of very thin Cu layers on the pristine and functionalized multiwall carbon nanotubes (f-MWCNTs) using both physical (electron beam evaporation (EBE)) and chemical (electrochemical deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Continuous monitoring of H 2 S using gas sensors in vital refinery areas is essential for promptly detecting potential risks. The implementation of alarms and automatic shutdown systems for increased H 2 S levels enhances safety, ensuring a swift response and minimizing hazards [90]. Furthermore, the deployment of corrosion probes, coupons, or ultrasonic thickness gauges effectively evaluates corrosion rates on metal surfaces exposed to H 2 S-containing environments.…”
Section: Continuous Monitoringmentioning
confidence: 99%
“…Continuous monitoring of H 2 S using gas sensors in vital refinery areas is essential for promptly detecting potential risks. The implementation of alarms and automatic shutdown systems for increased H 2 S levels enhances safety, ensuring a swift response and minimizing hazards [90]. Furthermore, the deployment of corrosion probes, coupons, or ultrasonic thickness gauges effectively evaluates corrosion rates on metal surfaces exposed to H 2 S-containing environments.…”
Section: Continuous Monitoringmentioning
confidence: 99%
“…Among these techniques, resistive gas sensing is of particular interest due to the low cost, high stability and sensitivity of the sensors [1]. Although the use of resistive sensors is hampered by their low selectivity and high operational temperature, chemically modified carbon materials are known to overcome these drawbacks [2]. In our previous work, we demonstrated that these disadvantages may be overcome by using dehydrofluorinated polyvinylidene fluoride (PVDF) as a sensing material [3].…”
Section: Introductionmentioning
confidence: 99%
“…Such material is denoted as "polyyne-polyene" in our studies. Such notation indicates that the obtained material has a chain-like structure, which is comprised from both sp-(polyynic) and sp 2 -hybridized (polyenic) linear fragments. In our previous studies, such structures were confirmed as a result of the dehydrohalogenation of PVDC [8] and PVDF [3].…”
Section: Introductionmentioning
confidence: 99%